Measuring Work Stress From Work-Life Balance and Workload During Covid-19 Pandemic - Marcheila, Syahna Dwialdena; Safitri, Rini (BISNIS, 2022)
This study aims to analyze work stress from work-life balance and workload. The population that is used in this study are all employees at the Directorate General of Islamic Education (DGIE), Ministry of Religious Affairs of the Republic of Indonesia (MORARI) with a sample of 212 employees. The method of determining the sample uses the probability sampling method with a simple random sampling approach. This study uses a type of research (explanatory research) with a quantitative approach. Collecting data using a questionnaire and then analyzed using PLS with WarpPLS 7.0 software. The results of this study indicate that workload has a positive and significant effect on work stress. Workload has a significant negative effect on work-life balance, work-life support has a significant and negative effect on work stress. Worklife balance can mediate the relationship between workload and work stress.